One year double blind study of high vs low frequency subcallosal cingulate stimulation for depression. (January 2018) - Eitan, Renana; Fontaine, Denys; Benoît, Michel; Giordana, Caroline; Darmon, Nelly; Israel, Zvi; Linesky, Eduard; Arkadir, David; Ben-Naim, Shiri; Iserlles, Moshe; Bergman, Hagai; Hulse, Natasha; et al.
Abstract: Subcallosal Brodmann's Area 25 (Cg25) Deep Brain Stimulation (DBS) is a new promising therapy for treatment resistant major depressive disorder (TR-MDD). While different DBS stimulating parameters may have an impact on the efficacy and safety of the therapy, there is no data to support a protocol for optimal stimulation parameters for depression. Here we present a prospective multi-center double-blind randomized crossed-over 13-month study that evaluated the effects of High (130 Hz) vs Low (20 Hz) frequency Cg25 stimulation for nine patients with TR-MDD. Four out of nine patients achieved response criteria (≥40% reduction of symptom score) compared to mean baseline values at the end of the study. The mean percent change of MADRS score showed a similar improvement in the high and low frequency stimulation groups after 6 months of stimulation (−15.4 ± 21.1 and −14.7 ± 21.1 respectively). The mean effect at the end of the second period (6 months after cross-over) was higher than the first period (first 6 months of stimulation) in all patients (−23.4 ± 19.9 (n = 6 periods) and −13.0 ± 22 (n = 9 periods) respectively). At the end of the second period, the mean percent change of the MADRS scores improved more in the high than low frequency groups (−31.3 ± 19.3 (n = 4 patients) and −7.7 ± 10.9 (n = 2 patients) respectively). Given the small numbers, detailed statistical analysis is challenging. Nonetheless the results of this study suggest that long term high frequency stimulation might confer the best results. Larger scale, randomized double blind trials are needed in order to evaluate the most effective stimulation parameters. Highlights: High (130 Hz) vs low (20 Hz) frequency Cg25 deep brain stimulation for depression. Effect at 6 months after cross-over was higher than first 6 months of stimulation. MADRS scores improved more in high than low frequency groups. Long-term high frequency stimulation might confer the best results. Larger scale trials are needed to evaluate the most effective stimulation parameters.